Covert channel: network steganography deployment - Md Ali, Nurul Majdi (Faculty of Information Technology and Quantitative Sciences, 2005)
Steganography is one of the major techniques used to hide the existence of communication that lies between two overt parties. Steganography also denoted by art of hiding communication. This work relates the areas of steganography, network protocols and security for practical data hiding in communication networks employing TCP/IP. This project major focus is to deploy steganography on network protocol using covert_TCP tool. This tool uses 3 methods in order to employ steganography at TCP/IP header; IP identification encoding, TCP sequence number encoding and ACK “bouncing” server method. We also employ network steganography in two different network environment which is on transmission on single host (loopback interface) and inter local area network. After that phase, we analyze packet income and out the network. We used network sniffer tool, tcpdump to dump all the packet and analyze the accuracy of the data transmit using covert channel as employ by covert_TCP.